KESEHATAN OPTIMAL DI MASA KEHAMILAN MELALUI KEGIATAN OLAHRAGA: LITERATURE RIVIEW - Kevin Putra Danuarta Nababan; Yuda Aryansyah Dalimunte; Jhan Riedho Syahputra Purba; Kevin Arjun Barasa; Muammar Muammar; Leonardo Lumbantobing; Nurhamida Sari Siregar; Randi Kurniawan (Jurnal Keluarga Sehat Sejahtera, 2025)
Pregnancy is accompanied by physical, hormonal, and psychological changes that can cause complaints such as back pain, constipation, hypertension, and sleep disorders. If not managed, these conditions can affect the health of the mother and fetus. One recommended strategy is regular exercise. This study examines the benefits of exercise, factors influencing physical activity, and appropriate types of exercise through a review of seven articles, six national journals, and one international journal (2017–2025). The results show that light to moderate exercise, such as prenatal exercises, yoga, walking, and swimming, maintains physical health and reduces stress, anxiety, and depression. Sociodemographic factors influence participation, while myths are a barrier. It is concluded that exercise is important as a promotive-preventive strategy, and further research needs to focus on community interventions.